2014
DOI: 10.1038/ejhg.2014.205
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the mutation spectrum in 182 Spanish probands with craniosynostosis: identification and characterization of novel TCF12 variants

Abstract: Craniosynostosis, caused by the premature fusion of one or more of the cranial sutures, can be classified into non-syndromic or syndromic and by which sutures are affected. Clinical assignment is a difficult challenge due to the high phenotypic variability observed between syndromes. During routine diagnostics, we screened 182 Spanish craniosynostosis probands, implementing a four-tiered cascade screening of FGFR2, FGFR3, FGFR1, TWIST1 and EFNB1. A total of 43 variants, eight novel, were identified in 113 (62%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
55
2
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(69 citation statements)
references
References 28 publications
8
55
2
4
Order By: Relevance
“…Clinical presentation of ERF mutations varies from a mild Crouzon-like picture to non-syndromic craniosynostosis. Further published information to augment the original clinical descriptions [28] is still scanty; surprisingly, in view of the relatively high frequency in the Oxford cohort, Paumard-Hernandez et al [29] did not identify any ERF mutations in a series of 69 undiagnosed craniosynostosis cases. Chaudhry et al [30] described two subjects with ERF mutations, who had features overlapping those originally reported.…”
Section: Syndromic Craniosynostosismentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical presentation of ERF mutations varies from a mild Crouzon-like picture to non-syndromic craniosynostosis. Further published information to augment the original clinical descriptions [28] is still scanty; surprisingly, in view of the relatively high frequency in the Oxford cohort, Paumard-Hernandez et al [29] did not identify any ERF mutations in a series of 69 undiagnosed craniosynostosis cases. Chaudhry et al [30] described two subjects with ERF mutations, who had features overlapping those originally reported.…”
Section: Syndromic Craniosynostosismentioning
confidence: 99%
“…The single largest contributor to these diagnoses is TCF12 , which encodes a partner protein of TWIST1 particularly critical for coronal suture development [27]. Two follow-up studies have confirmed the importance of TCF12 mutations in coronal craniosynostosis, both in the context of familial mutations [37], and in a more general screen of craniosynostosis [29]. Given the haploinsufficiency mechanism of TCF12 mutations, heterozygous deletions are also expected to be pathogenic and this has been confirmed in two reports [38, 39].…”
Section: Non-syndromic Craniosynostosismentioning
confidence: 99%
“…Although 81% of the individuals with TCF12 mutations presented with apparent cNCS, some of the affected individuals had developmental delays and dysmorphic features overlapping with the Saethre-Chotzen syndrome [Sharma et al, 2013]. More recently, the phenotypic spectrum of TCF12 mutations has been extended to include possible facial and limb anomalies, and intellectual disability [Di Rocco et al, 2014; Le Tanno et al, 2014; Paumard-Hernandez et al, 2015; Piard et al, 2015]. Based on these observations, it is reasonable to recommend TCF12 testing for all patients with cCS, with or without associated anomalies.…”
Section: Genetic Etiopathogenesis Of Craniosynostosismentioning
confidence: 99%
“…No mutations or deletions were detected in FGFR1 , FGFR2 , FGFR3 , TWIST , EFNB1 , and TCF12 [Paumard-Hernández et al, 2015]. Subsequently, a SNP-array was performed.…”
Section: Resultsmentioning
confidence: 99%
“…DNA from the patient was screened for mutations in the craniosynostosis genes as previously described [Paumard-Hernández et al, 2015] and for chromosomal rearrangements using the Infinium Cyto-SNP-850K BeadChip (Illumina), according to the manufacturer's instructions and analyzed on an Infinium iScan TM System platform (Illumina). The data was analyzed using the GenomeStudio TM software (Illumina).…”
Section: Methodsmentioning
confidence: 99%